2008
DOI: 10.1101/gad.1720008
|View full text |Cite
|
Sign up to set email alerts
|

The Iws1:Spt6:CTD complex controls cotranscriptional mRNA biosynthesis and HYPB/Setd2-mediated histone H3K36 methylation

Abstract: Many steps in gene expression and mRNA biosynthesis are coupled to transcription elongation and organized through the C-terminal domain (CTD) of the large subunit of RNA polymerase II (RNAPII). We showed recently that Spt6, a transcription elongation factor and histone H3 chaperone, binds to the Ser2P CTD and recruits Iws1 and the REF1/Aly mRNA export adaptor to facilitate mRNA export. Here we show that Iws1 also recruits the HYPB/Setd2 histone methyltransferase to the RNAPII elongation complex and is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
263
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(282 citation statements)
references
References 67 publications
16
263
1
Order By: Relevance
“…In this regard it is known that IWS1 interacts with the CTD of the large subunit of RNAPII complex through Spt6 (ref. 43). During the reviewing process of this manuscript, Gérard et al published an independent study, which confirmed the existence of a LEDGF/p75-IWS1-Spt6 triple complex that was suggested to have an important function during HIV latency 46 .…”
Section: Jpo2 Interacts With the Ibd Through A Disordered Regionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this regard it is known that IWS1 interacts with the CTD of the large subunit of RNAPII complex through Spt6 (ref. 43). During the reviewing process of this manuscript, Gérard et al published an independent study, which confirmed the existence of a LEDGF/p75-IWS1-Spt6 triple complex that was suggested to have an important function during HIV latency 46 .…”
Section: Jpo2 Interacts With the Ibd Through A Disordered Regionmentioning
confidence: 71%
“…This complex recruits HYPB/Setd2 histone methyltransferase, which controls H3K36me3 methylation, affecting co-transcriptional pre-mRNA splicing and export 42,43 . Because LEDGF is linked to both alternative splicing and interaction with H3K36me3, we chose to experimentally investigate the interaction between LEDGF/p75 and IWS1.…”
Section: Jpo2 Interacts With the Ibd Through A Disordered Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a C-terminal fragment of murine Spt6 (residues 1162-1726) that contains the SH2 domain did not bind to a Ser2-phosphorylated tandemrepeat CTD peptide, but bound to the N-terminal half of the CTD, which contains a stretch of 15 consensus repeats. 66 Thus, interactions that are not predicted by our modeling (Fig. 4) may occur between the SH2 domain and a longer CTD peptide.…”
Section: The Sh2 Domain Is Insufficient For Binding Short Ctd Phosphomentioning
confidence: 72%
“…Considering that these HMTs have different domain architectures and possibly different expression patterns, it is reasonable to postulate that the different H3K36 HMTs play distinct roles and cooperate to subtly regulate histone methylation and gene expression, thus controlling complicated developmental processes. Although H3K36 methylation has been implicated in multiple molecular functions including transcriptional elongation, suppression of cryptic transcription and mRNA export (33)(34)(35)(36), it remains unclear whether H3K36 methylation contributes to any specific developmental processes. In this study, we identified the genes altered by the Hypb disruption, some of which might be directly or indirectly related to the loss of H3K36me3, thus allowing study of potential functions of Hypb and H3K36 methylation on different genes.…”
Section: Discussionmentioning
confidence: 99%